Marginalia kultury: o obrazach ciąży i ich znaczeniach w kulturze doświadczenia potocznego - Kloch, Zbigniew (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2009)
On the Margins of Culture: Images of Pregnancy and their Meanings in the Culture of Daily Experience This essay describes meanings attributed to images of pregnancy in contemporary culture, to their idiomatic expressions and to fashions associated with pregnancy. It considers also semiotic and sociological contexts that are being modeled through these meanings. Pregnancy appears then as a symbol of prevailing values, a sign of social standing and ideological convictions. This essay contributes to the understanding and explanation of how meanings are formed in the culture of daily experience.